Near-Infrared Spectroscopy during the Verbal Fluency Task before and after Treatment with Image Exposure and SSRI Therapy in Patients with Obsessive-Compulsive Disorder - Mari Nakanishi; Harumi Oshita; Yoshihiro Tanaka; Ayako Inoue; Chiwa Kawashima; Kana Okamoto; Shunsuke Kobayashi; Yoshinobu Ishitobi; Taiga Ninomiya; Jotaro Akiyoshi (Case Reports in Psychiatry)
Drug therapy with selective serotonin reuptake inhibitors (SSRIs) has been used as a treatment for obsessive-compulsive disorder (OCD). In the present case report, exposure therapy was used in addition to escitalopram (20 mg) to treat a 28-year-old female patient with OCD for 6 months. Her obsessive-compulsive symptoms comprised thoughts of words such as rape, crematorium, neck hanging, unhappy, death, die, and kill and images such as a shelf of gods, a shrine, a Buddhist altar, the sun, the sky, and the faces of her parents, siblings, and relatives. As exposure therapy, she was asked to view the images associated with these symptoms three times a day along with drug therapy. With the combination of drug and exposure therapies, her obsessive-compulsive symptoms improved within 6 months, with no interference in her daily life. Multichannel near-infrared spectroscopy (NIRS) showed improvement of brain function in the temporal and frontal lobes after treatment. These results suggest that NIRS can be used as an indicator of brain function improvement in patients with OCD.